Aktivitas antioksidan dan karakteristik sensori teh herbal daun sirsak dengan penambahan daun mint - Dewi Fortuna Ayu; Hary Love Frendra Ramadhan; Evy Rossi; Imelda Yunita (Institution for Industrial Research and Standardization of Industry - Padang, 2024)
Herbal tea is functional drinks made from ingredients that can provide benefits for health, one of them as a source of antioxidants. This study aimed to obtain the best additional mint leaves on antioxidant activity and sensory characteristics of soursop leaves herbal tea. The research was conducted experimentally using a completely randomized design with six treatments and three replications. The data of antioxidant activity were analyzed descriptively, while moisture, ash, polyphenol, and the sensory characteristics of herbal tea were statistically analyzed using analysis of variance and followed by Duncan's multiple range test at 5% to determine the difference in each treatment. The study's treatments of additional mint leaves were at levels 10, 20, 30, 40, and 50% of the soursop leaves weight (b/b). The results showed that the additional mint leaves significantly affected antioxidant activity, moisture, ash, polyphenol content, and sensory evaluation. The best treatment was additional mint leaves of 50% which had 29.08 ppm IC50, 8.68% moisture, 7.97% ash, and 37.66% polyphenol content. The herbal tea was brown, slightly unpleasant aroma, non-spicy taste, and overall assessment hedonically was favored by panelists with score of 4.04.